Entrelazamiento toma de decisiones-procesos gerenciales en el modelo cooperativista (Agroindustria, Sociedad y Ambiente, 2018)
The socioeconomic situation of Venezuela is a reason to promote solidarity economy and one of the expressions of this, is the cooperativism, business model based on inclusion and sustainability that offers a path towards economic, social and political justice. In this, decision making is conditioned by a set of principles that legitimize it. It is for this reason, that this study seeks to interpret how the interlacing that exists between decision making in relation to managerial processes occurs, , that is to say, that intricate relationship that exists between a decision and the fact of planning, organizing, ordering, coordinating and controlling among others that emerge within the dynamics of the context. The investigation was approached from the interpretative paradigm. The method, Grounded Theory that allowed generating an interpretation of the relationship that exists between decision making and management processes based on the perceptions of the members of the cooperative. Among the findings highlight that participation in the administrative management it represents a source of moral encouragement and that the motivation comes given all for being involved in Decision Making This process is based on transparency and they deliver it to the best of their efforts and knowledge to achieve common goals.